Penerapan Unplugged Coding Angka dalam Meningkatkan Kemampuan Numerasi Anak Usia 4–5 Tahun di RA Plus An Nuha Sumberejo - Riya Yuliatin; Ulya Ainur Rofi’ah (Khirani: Jurnal Pendidikan Anak Usia Dini, 2026)
This research was motivated by the low numeracy skills of children aged 4–5 years at RA Plus An Nuha Sumberejo Rengel, particularly in recognizing number symbols, counting, understanding simple patterns, and matching quantities with number symbols. Numeracy learning, which was still conducted conventionally, caused children to be less active and easily bored during the learning process. Therefore, an innovative learning approach that is more engaging and suitable for early childhood characteristics was needed, one of which was through the implementation of Unplugged Coding Numbers. This study aimed to determine the implementation of Unplugged Coding Numbers in numeracy learning and to identify the improvement of numeracy skills among children aged 4–5 years after the implementation of the activity. This study employed a Classroom Action Research (CAR) approach using the Kemmis and Mc. Taggart model, which was conducted in two cycles consisting of planning, action, observation, and reflection stages. The participants of this study were 11 children aged 4–5 years at RA Plus An Nuha Sumberejo Rengel in the 2025/2026 academic year. Data collection techniques included observation, interviews, and documentation. The data were analyzed using descriptive quantitative and qualitative methods through percentage calculations of children’s numeracy skill development. The results showed that the implementation of Unplugged Coding Numbers was able to create a more active, interactive, and enjoyable numeracy learning environment through the use of concrete media such as number cards, coding path boards, pattern games, and number coding worksheets. In addition, children’s numeracy skills showed significant improvement. The pre-cycle stage obtained a percentage of 26,82%, which increased to 53,18% in Cycle I and further increased to 92,27% in Cycle II under the category of Very Well Developed. These findings indicate that the implementation of Unplugged Coding Numbers was effective in improving the numeracy skills of children aged 4–5 years at RA Plus An Nuha Sumberejo Rengel in the 2025/2026 academic year.